The Influence of Organizational Culture and Self-Efficacy on the Motivation of Civil Servants at the UPTD Puskesmas Sungai Ambawang - Irfan Mahdi; Karya Ardiansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Organizational Culture and Self-Efficacy on the Motivation of Civil Servants at the UPTD Puskesmas Sungai Ambawang. This study employed a quantitative approach with an associative method. The research sample consisted of 50 respondents selected using a saturated sampling technique. Data were collected through interviews, questionnaires, and documentation. Data analysis was conducted using multiple linear regression with the assistance of SPSS through validity tests, reliability tests, classical assumption tests, and hypothesis testing using the t-test and F-test. The results show that all research instruments were valid and reliable, and the data met the assumptions of normality, linearity, and the absence of multicollinearity. Partially, Organizational Culture has a positive and significant effect on Motivation, with a t-count value of 3.078 and a significance value of 0.003. Self-Efficacy also has a positive and significant effect on Motivation, with a t-count value of 2.300 and a significance value of 0.026. Simultaneously, Organizational Culture and Self-Efficacy have a significant effect on Motivation, with an F-count value of 31.506 and a significance value of 0.001. The correlation coefficient (R) value of 0.757 indicates a strong relationship, while the coefficient of determination (R²) value of 0.573 shows that 57.3% of Motivation can be explained by Organizational Culture and Self-Efficacy, while the remaining portion is influenced by other variables outside this study.